Development of integrated spectral sun-photometer based on embedded Linux OS. Issue 1 (April 2021) - Zhaoyang, Qi; Fengying, Sun; Jianyu, Li; Wenyue, Zhu; Wenqing, Xu; Gang, Xu; Yao, Huang
Abstract: Accurate detection of solar irradiance has important application value for theoretical research on climate change and atmospheric analysis, so this paper proposes the integrated spectral sun-photometer to enrich methods of obtaining the solar irradiance and entire atmospheric transmittance. With the ARM microprocessor as central processing unit and Linux OS as the software platform, the two-dimensional turntable and grating spectrometer are combined to construct sun-photometer which can measure continuous wavebands. This article advances the solution scheme to realize data transmission between microcontroller and turntable through CANopen communication. Meanwhile, the spectrometer based on USB communication protocol is used to obtain spectrum from visible to near-infrared band. In addition, both the multiple task operating system Linux and application framework Qt are employed to design friendly user-interface and display real-time process images, which would simplify and integrate the solar radiometer. After Langley calibration is used to calculate the constants to achieve calibration of instrument in spectral band, measured data of the radiometer and results of the DTF solar radiometer are compared and analysed, which confirms the reliability of integrated sun-photometer.